Knowledge, attitude, and practices towards epilepsy among university students in South India - Silvia, L. Caroline (International Journal of Research in Medical Sciences, 2022)
Background: Epilepsy is one of the common chronic neurological problem affecting people of all ages. Ironically it is also associated with much stigma attached to it. Knowledge about the disease is essential to dispel the myths and misbeliefs. The objective of this study were to evaluate the awareness on epilepsy among the students in a private university and to compare the levels of awareness between health and non-health care students. Methods: A self-administered questionnaire was applied to 830 students (healthcare group 1- 410; non-health care group 2- 420) at SRM University, Tamil Nadu. Results: Of the 830 students (489 males, 341 females), 93.6% heard about epilepsy. Only 48% have seen a person with epilepsy. One fifth of them link epilepsy with mental illness. 6% believe it to be contagious. A relevant portion of the sample have negative attitudes towards epilepsy. Conclusions: Though majority had reasonable knowledge of epilepsy, there is lack of information among students. Awareness programs should target students-the future pillars of the society.